Refraction changes in children developing convergent or divergent strabismus. - Abrahamsson, M. (1992)
Strabismus and amblyopia were studied in a cohort of children born in 1979 or 1980 in the area of Västerås, Sweden. Forty percent of the children had participated in a voluntary eye examination at 1 year of age. All children diagnosed as strabismic and/or amblyopic between 1979 and 1988 at any of the three eye clinics in the area were included in this study. Strabismic cases were mostly detected by the parents while microstrabismus and straight eye amblyopia were found at the general 4 years of age screening at children's health centres. In 57 cases with (n = 31) and without amblyopia (n = 41) it was possible to obtain several refraction values between 1 and 6 years of age. In this study we concentrated on manifest esotropia and exotropia. The aim of the study was to describe changes of refraction before and after onset of strabismus and to establish risk indicators that identified populations at risk of developing strabismus. We found that patients with esotropia show a more pronounced hypermetropia than exotropic cases at the time of detection of strabismus. This difference becomes more definite over time, since hypermetropia increased in the deviating eye in the esotropic cases while refractive errors remained stationary in most of the exotropic eyes. It was also apparent that anisometropia frequently developed after onset of strabismus in esotropic cases in contrast to exotropic cases. An increasing refractive error in the deviating esotropic eye could be combined with an emmetropisation of the fixating eye.